Progress and perspectives in the discovery of polychaete worms (Annelida) of the world - Wilson, Simon; Pamungkas, Joko; Costello, Mark J.; Glasby, Christopher J.; Read, Geoffrey B. (My University, 2019)
Despite the availability of well-documented data, a comprehensive review of the discovery progress of polychaete worms (Annelida) has never been done. In the present study, we reviewed available data in the World Register of Marine Species, and found that 11,456 valid species of Recent polychaetes (1417 genera, 85 families) have been named by 835 first authors since 1758. Over this period, three discovery phases of the fauna were identified. That is, the initial phase (from 1758 to mid-nineteenth century) where nearly 500 species were described by few taxonomists, the second phase (from the 1850’s to mid-twentieth century) where almost 5000 species were largely described by some very productive taxonomists, and the third phase (from the 1950’s to modern times) in which about 6000 species were described by the most taxonomists ever. Six polychaete families with the most species were Syllidae (993 species), Polynoidae (876 species), Nereididae (687 species), Spionidae (612 species), Terebellidae (607 species) and Serpulidae (576 species). The increase in the number of first authors through time indicated greater taxonomic effort. By contrast, there was a decline in the number of polychaete species described in proportion to the number of first authors since around mid-nineteenth century. This suggested that it has been getting more difficult to find new polychaete species. According to our modelling, we predict that 5200 more species will be discovered between now and the year 2100. The total number of polychaete species of the world by the end of this century is thus anticipated to be about 16,700 species.
PUBLISHED
Keywords: Biodiversity; Echiura; Marine; Polychaete worms (Annelida); Polychaeta; Pogonophora; Species discovery rate; Taxonomy; Vestimentifera